FLT3 signaling inhibition abrogates opioid tolerance and hyperalgesia while preserving analgesia - Antoine Jouvenel; Adrien Tassou; Maxime Thouaye; Jérôme Ruel; Myriam Antri; Jean-Philippe Leyris; Aurore Giraudin; Sylvie Mallié; Chamroeum Sar; Lucie Diouloufet; Corinne Sonrier; François Daubeuf; et al. (Nature Communications)
Abstract Navigating the duality of opioids’ potent analgesia and side effects, including tolerance and hyperalgesia, is a significant challenge in chronic pain management, often prompting hazardous dose escalation to maintain analgesic effects. The peripheral mu-opioid receptor (MOR) is known to mediate these contradictory effects. Here, we show that the fms-like tyrosine kinase receptor 3 (FLT3) in peripheral somatosensory neurons drives morphine tolerance and hyperalgesia in a male rodent model. We found that chronic morphine treatment increases FLT3 and MOR co-expression, and that inhibiting FLT3 represses MOR-induced hyperactivation of the cyclic adenosine monophosphate (cAMP) signaling pathway, mitigating maladaptive excitatory processes engaged after chronic morphine treatment. Furthermore, in postsurgical or inflammatory models of chronic pain, co-administering morphine with a FLT3-specific inhibitor not only prevents or suppresses tolerance and hyperalgesia but also potentiates the analgesic efficacy of morphine, without aggravating other morphine-induced adverse effects. Our findings suggest that pairing morphine with FLT3 inhibitors could become a promising avenue for chronic pain management to safely harness the power of opioids, without the risk of dose escalation. By enhancing morphine analgesic potency through FLT3 inhibition, this approach could minimize opioid dosage, thereby curtailing the risk of addiction and other opioid-related side effects.